Socio-Economic Transformation of Households Due to the Development of the New Joho Housing Complex in Joho Village, Sukoharjo - Zulkifli, Nur Aisyah; Muzdhalifah, Glory (GeoEdu Insight Journal, 2026)
Purpose of the study: This study aims to examine the socio-economic transformation of households following the development of the New Joho Housing Complex in Joho Village, Sukoharjo, between 2003 and 2011, focusing on land-use change, livelihood shifts, welfare levels, and social interaction patterns. Methodology: This study employed a descriptive quantitative design with a spatial approach. Land-use change was analyzed using Geographic Information System (GIS) overlay techniques with ArcView version 3.3. Data were collected through observation, documentation, and structured interviews. Sampling used purposive and random sampling methods, with 140 household heads selected using Isaac and Michael’s formula. Main Findings: The results show significant conversion of irrigated rice fields into residential areas, with 21.17 hectares transformed between 2003 and 2011. Agricultural employment declined by 15.71%, while non-agricultural occupations increased proportionally. Household welfare levels improved, particularly in the Prosperous Family Stage III category. However, the proportion of households with very strong social interaction decreased, indicating emerging social cohesion challenges. Novelty/Originality of this study: This study integrates GIS-based spatial overlay analysis with quantitative household socio-economic assessment within a single peri-urban locality over an extended period. By simultaneously examining land conversion, livelihood transition, welfare change, and social interaction patterns, it provides a multidimensional empirical framework that advances understanding of development-induced transformation in peri-urban communities.